An integrated fuzzy approach for evaluating remanufacturing alternatives of a product design - Xiaojun Wang; Hing Kai Chan (Journal of Remanufacturing, 2013)
Remanufacturing has emerged as a competitive strategy for manufacturers to tackle environmental and economic challenges. In this paper, an integrated fuzzy approach is developed for the evaluation of remanufacturing alternatives. Then, importance weights of main remanufacturing processes and evaluation criteria are obtained through fuzzy extent analysis. Fuzzy hierarchical TOPSIS is then applied to evaluate the alternatives. A case study is presented to demonstrate the applicability of the proposed approach. The analysis results show that it is a viable approach and can be used as an effective tool for design evaluation from the remanufacturing point of view. Finally, conclusions are discussed and future research directions are suggested.
Keywords: 650; Remanufacturing; Hierarchical model; Life cycle assessment; Fuzzy extent analysis; TOPSIS